1, 3‐Dioleoyl‐2‐palmitoyl glycerol (OPO)—Enzymatic synthesis and use as an important supplement in infant formulas. Issue 7 (2nd June 2021) - Ghide, Michael Kidane; Yan, Yunjun
Abstract: 1, 3‐dioleolyl‐2‐palmitate (OPO) is an important component of the human milk fat. Its unique fatty acid composition and distribution play an important role in proper infant growth and development. Owing to this, it has been attracting researchers and manufacturers to synthesize and commercialize OPO as an important human milk fat substitute added to infant formulas. In this review, the role of OPO in human milk, the benefits of OPO (sn‐2 palmitate)‐supplemented infant formulas over the conventional infant formulas on infant growth, and lipase‐catalyzed synthesis of OPO are discussed. Over the last 20 years of research on the benefits of OPO (sn2 palmitate)‐supplemented infant formulas are summarized. Similarly, studies carried out on lipase catalyzed production of OPO for the last 21 years (1999–2019) are also done focusing on the raw materials, sn1, 3‐regiospecific lipases, immobilization materials, and solvents used in the laboratory‐scale experiments. In addition, OPO‐based products currently in the market and future research trends are briefly covered in this review. Practical applications: This work focuses on lipase‐catalyzed synthesis of 1, 3‐dioleoyl‐2‐palmitoylglycerol (the most abundant triacyl glycerol in human milk fat) and its benefits to infants when it is added in infant formulas. Over the last 20 years of published research from the literature are summarized and future research trends for efficient OPO synthesis are also covered. This will provide current and future researchers on the field with the necessary background information on OPO synthesis and design their research plans accordingly for cost‐effective production of OPO and OPO‐supplemented infant formulas. Abstract : Scheme 1 Enzymatic synthesis of 1, 3‐Dioleoyl‐2‐palmitoylglycerol (OPO) and its use as an important infant formula supplement. Here, Palmitic acid (PA)‐rich fats and Oleic acid (OA) or OA‐rich vegetable oils undergo (inter) esterification reactions under the catalysis of Sn1, 3 regiospecific lipase to produce OPO. OPO (the most abundant triacyl glyceride in human milk fat) is added into infant formulas to help in proper infant growth and development similar to breast‐fed infants